2018
DOI: 10.1016/j.bpj.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Single-Cell RNA-Seq of Microorganisms

Abstract: Single-cell transcriptome analysis through next-generation sequencing (single-cell RNA-seq) has been used broadly to address important biological questions. It has proved to be very powerful, and many exciting new biological discoveries have been achieved in the last decade. Its application has greatly improved our understanding of diverse biological processes and the underlying molecular mechanisms, an understanding that would not have been achievable by conventional analysis based on bulk populations. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 68 publications
0
31
0
Order By: Relevance
“…In general, these studies already provide the basic framework for SCT; however, they have so far only been carried out on model organisms, and many technical challenges still remain such as the inefficient transcriptome coverage, biased amplification, and throughput (Picelli 2017 ; Chen et al 2017 ; Zhang et al 2018 ). Direct-RNA methods that do not require pre-amplification, e.g., Oxford Nanopore sequencing systems, would be ideal to cut out amplification bias (Garalde et al 2018 ).…”
Section: Technical Problems Recent Advances and Future Challengesmentioning
confidence: 99%
“…In general, these studies already provide the basic framework for SCT; however, they have so far only been carried out on model organisms, and many technical challenges still remain such as the inefficient transcriptome coverage, biased amplification, and throughput (Picelli 2017 ; Chen et al 2017 ; Zhang et al 2018 ). Direct-RNA methods that do not require pre-amplification, e.g., Oxford Nanopore sequencing systems, would be ideal to cut out amplification bias (Garalde et al 2018 ).…”
Section: Technical Problems Recent Advances and Future Challengesmentioning
confidence: 99%
“…This is particularly relevant for exploring synthetic cells, for which the input amount of DNA/RNA could be very low depending on experimental system or scientific question and hence face challenges similar to sequencing single microorganisms. [34] Furthermore, the vast majority of single-cell sequencing is currently done using short-read sequencing approaches. This sequencing approach is inapplicable for long repetitive sequences and heavily relies on pre-amplifications of DNA/RNA.…”
Section: Challengesmentioning
confidence: 99%
“…However, reports of its applications in prokaryotic cells are scarce up to now. One of the reasons is that the small amount of RNA is normally undetectable, as well as lacking polyadenylated tails on mRNA and short half-life time of RNA [47]. To our knowledge, the first study of prokaryotic single-cell transcriptome analysis was reported by Kang et al [20,48].…”
Section: Characterization Of Intracellular Componentsmentioning
confidence: 99%